Impact of morphological parameters onto simulated light scattering patterns - Skorupski, Krzysztof; Mroczka, Janusz; Riefler, Norbert; Oltmann, Hergen; Will, Stefan; Wriedt, Thomas (Journal of Quantitative Spectroscopy & Radiative Transfer, 2013)
We have investigated the impact of the variation of various parameters of fractal aggregates on simulated light scattering patterns. Static light scattering is commonly used to measure soot in a flame and such a study could help to improve experimental approaches. Aggregate models, used for our light scattering simulations, are based on real soot structures that can be found under laboratory conditions in a premixed ethane/air flame (McKenna-type burner, equivalence ratio phi = 2.5). Our work was not focused on modeling and analysis of aggregates that are typically encountered in the atmosphere, therefore the results might be of limited interest to climate scientists. In our study, the variation of all parameters that enter into the standard fractal equation were investigated. Additionally effects when varying the overlap of primary particles, the incident wavelength and the complex refractive index are discussed. For numerical simulations two different codes were used, the T-Matrix (when particles are in point contact) and the DDScat program (which is capable of performing light scattering simulations by overlapping spheres). Comparisons between these two methods show very good agreement. The results demonstrate that the radius of gyration is responsible for the amount of light scattered towards the back direction while the total volume of an aggregate defines the shape of the light scattering patterns. Small changes of the fractal dimension can be neglected (provided that the fractal prefactor is accordingly modified in a suitable way). The overlap level, if the radius of gyration is kept constant, introduces barely visible changes to the light scattering diagrams which suggest that a simple aggregate model, composed of particles being in point contact, can be used instead of a structure in early sintering stage when overlap of primary particles is not so high. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Fractal aggregates; Light scattering; T-Matrix; DDScat